Families of exact solutions of Biswas-Milovic equation by an exponential rational function method - Ghanbari, Behzad; İnç, Mustafa; Yusuf, Abdullahi; Baleanu, Dumitru; Bayram, Mustafa (Tbilisi Centre Math Sci, 2020)
In this paper, we introduce generalized exponential rational function method (GERFM) to obtain an exact solutions for the Biswas-Milovic (BM) equation with quadratic-cubic and parabolic nonlinearities. A wide range of closed solutions are acquired. The most important feature of the new method is that it is very effective and simple. The main merits of the proposed is that it gives more general solutions with some free parameters and can be applied to other types of nonlinear partial differential equations.Some interesting Figures for the physical features of some of the obtained solutions are also presented.
Keywords: exact solutions; optical solutions; exponential rational function method; nonlinear optical fibers; nonlinear Biswas-Milovic equation